Eco-Theology Based Islamic Boarding School: Green Islamic Boarding School Education Transformation Strategy and Sustainable Infrastructure Towards Zero-Waste Boarding School at Nurul Jadid Paiton Probolinggo Islamic Boarding School - Rifa'i (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The integration of environmental sustainability into faith-based education remains a critical yet underdeveloped area in global educational discourse, particularly in contexts where religious values hold strong influence over learners’ worldviews and behaviors. Despite the presence of ecological principles in Islamic teachings, their implementation within formal educational systems is often fragmented and insufficiently translated into structured pedagogical practices. This study aims to examine how eco-theological principles can be systematically operationalized through a Green Islamic Boarding School model at Nurul Jadid, Indonesia, by integrating curriculum, pedagogy, institutional culture, and sustainable infrastructure. Using a qualitative case study approach, data were collected through observations, in-depth interviews, and document analysis, focusing on key initiatives such as ecological project-based learning, the Clean Pesantren program, greening activities, and the Integrated Waste Management Installation (IPST). The findings reveal that eco-theological values become significantly more effective when enacted through experiential learning, institutional routines, and system-based environmental practices that reinforce students’ ecological awareness and behavior. The integration of religious concepts such as khalīfah fī al-arḍ and amanah provides a strong moral and spiritual foundation that enhances the sustainability of behavioral change. This study offers a novel contribution by conceptualizing and operationalizing an Eco-Theological Transformative Education Model that integrates ethical, pedagogical, and structural dimensions into a unified framework. The findings extend existing sustainability education theories by demonstrating how faith-based institutions can function as transformative agents in addressing environmental challenges. Therefore, this research provides important theoretical and practical implications for the development of contextually grounded sustainability education in faith-based institutions worldwide.